2012
DOI: 10.1159/000336969
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Conserving Therapy for Early-Stage Breast Cancer in Chinese Women: A Meta-Analysis of Case-Control Studies

Abstract: Background: Breast cancer has a high incidence worldwide, while Chinese patients have some special characteristics compared to Western patients. A meta-analysis was carried out to determine the effectiveness of breast-conserving therapy (BCT) or mastectomy therapy (MT) for early-stage breast cancers in Chinese women. Methods: A fully recursive literature search was conducted in the Chinese Biomedical Literature Database. Case-control trials were considered for inclusion. Analyses were carried out using the Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(14 reference statements)
2
2
0
Order By: Relevance
“…This is consistent with the results of several randomized clinical trials published from 1980 to 2008 that showed no significant difference in OS ( 2 , 28 - 37 ) and DFS ( 2 , 28 , 34 , 36 ) between stage I-II (T1-2, N0-1) IBC patients who underwent BCS plus radiation and radical or modified radical mastectomy at 5-20 years of follow-up. Similar to the results of this study, a meta-analysis including 25 Chinese Case-Control Studies from 2004 to 2010 showed that there was no significant difference between 3-year and 5-year OS of IBC patients with early stage in the BCS group and the MT group ( 38 ). We believe that large randomized clinical trials can better eliminate confounders and compare the impact of the two surgical methods on the survival more objectively.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the results of several randomized clinical trials published from 1980 to 2008 that showed no significant difference in OS ( 2 , 28 - 37 ) and DFS ( 2 , 28 , 34 , 36 ) between stage I-II (T1-2, N0-1) IBC patients who underwent BCS plus radiation and radical or modified radical mastectomy at 5-20 years of follow-up. Similar to the results of this study, a meta-analysis including 25 Chinese Case-Control Studies from 2004 to 2010 showed that there was no significant difference between 3-year and 5-year OS of IBC patients with early stage in the BCS group and the MT group ( 38 ). We believe that large randomized clinical trials can better eliminate confounders and compare the impact of the two surgical methods on the survival more objectively.…”
Section: Discussionsupporting
confidence: 85%
“…Cai X with his coleagues found that BCT was the better choice than MT for Chinese women with earlystage breast cancer eventhough they worked on non rendomized trials. 8 The similar results were found by Vila J and colleagues. For them, mastectomy provides better OS compared to breast conserving surgery followed by whole breast radiotherapy in early breast cancer patients aged 40 years or younger.…”
Section: Risk Of Biassupporting
confidence: 78%
“…Another meta-analysis performed with non-randomised studies reported that the 3 year or 5 year overall survival, was not statistically different between the BCT group and the mastectomy group. 8 For this meta-analysis, the included studies reported the outcome as dichotomous data.…”
mentioning
confidence: 99%
“…LRFS and DRFS were not significantly different between the BCS and MT groups [ 34 , 35 ] as well as like some studies said, following neoadjuvant chemotherapy [ 36 , 37 ]. However, some researchers found that BCS patients had higher LR after NAC, perhaps because the surgical margins became difficult to accurately assess [ 38 ], some studies reported contrary results that MT group had higher LR rate compared with BCS group [ 18 , 39 ].…”
Section: Discussionmentioning
confidence: 76%